ANALISIS SWOT BISNIS LAUNDRY UD RAFA LAUNDRY KLINDOCARE DI DURI PROVINSI RIAU (STUDI FORMULASI STRATEGI BERSAING) - M. Fidel Khasandra; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Rafa Laundry Klindocare Duri. This business is engaged in cloth washing services. The purpose of this research is to formulate competitive strategy formulation at Rafa Laundry Klindocare. This research is descriptive research with qualitative approach, where in this research do not use population and sample only use key informant to get information needed. The data used are primary and secondary data. From the analysis results can be seen that there are several alternative strategies that can be used as a tool to win the competition on Rafa Laundry industry. One strategy that can be applied based on the utilization of existing opportunities by minimizing existing weaknesses.Keywords: SWOT (Strengths, Weakness, Opportunity, Threat), SWOT Analysis, Alternative Strategy Rafa Laundry Klindocare